On the typification and nomenclature of Rhododendron ×intermedium (Ericaceae) - Sosnovsky, Yevhen; Nachychko, Viktor; Mráz, Patrik (Phytotaxa, 2017)
We discuss the typification and nomenclature of the name Rhododendron ×intermedium (Ericaceae). As the name R. ×intermedium Wenderoth is invalid, the earliest legitimate name for R. ferrugineum × R. hirsutum hybrid is the name published by Tausch. We designate one collection from PRC as the lectotype and two other specimens from PRC are considered to be a part of the original material. A list of R. ×intermedium synonyms is provided and two specimens from IBF are designated as the neotypes of two heterotypic synonyms, namely R. ×halense and R. ×hirsutiformum.